Análise numérica 3D de spray de etanol em câmara com contrapressão - Roberto Ribeiro Schor (2018)
Due to the new regulations in environment laws the new emission standards are increasingly more restrictive. Therefore, new engine technologies has been researched to make the engines more fuel efficient and to decrease the emissions. The direct injection is one of those new technologies, to substitute the old port fuel injection, allowing to improve the control of the cylinder combustion. For this, specially in the cases of stratified strategy or compression ignition engines, the control of the spray injection is very important to control of the air/fuel ratio through the cylinder. The formation of the air fuel mixture, and consequently the evolution of the spray and its atomization combined with the diffusion and evaporation of the fuel in the air together with the charge motion in the combustion chamber are very important for controlling and optimizing the combustion. Since the optical access to the combustion chamber is difficult to access or prohibitive due to costs, the most coherent technique for analyzing the effects of spray in the air mixture in the combustion chamber is the numerical simulation approach. The aim of this dissertation is to develop and validate a Computer Fluid Dynamics (CFD) methodology for modeling and analyzing the ethanol Spray generated by a pressure-swirl automotive injector in a chamber with back pressure utilizing the software OpenFOAM an open source code. The methodology employed to evaluate the ethanol spray pattern with OpenFOAM was validated with experimental data up to 5 bar of vessel pressure. The initial fuel drop size distribution was described by two models, Rosin Rammler and LISA, and the subsequent droplet break up was described by three models, Diwakar, KHRT and TAB for vessel pressures of 1 bar and 5 bar. The droplet mean diameter value was validated with experimental data at 1 bar. For pressures up to 5 bar, among the evaluated models, the optimum models which were able to capture the flow pattern of the ethanol spray are the atomization model LISA with the secondary break up model TAB and the PDF function Rosin Rammler with either KHRT or TAB break-up models. Concluding, for the usual cases of injection in spark ignition engines the models implemented in this dissertation were validated against experimental data and can be utilized in more complex models, e.g. dynamic spray simulation with a moving mesh.